FRICTION STIR WELDING AND AEROSPACE APPLICATIONS - Serdar Dalkılıç (Havacılık ve Uzay Teknolojileri Dergisi, 2012)
The difficulty of producing welded joints having high strength and fatigue and corrosion resistance with 2xxx and 7xxx series aluminum alloys which are widely used in aerospace industry has inhibited the use of joining aerospace structures by welding method. These aluminum alloys have been classified as non-weldable because of exhibiting poor solidification microstructure and porosity in the fusion zone. Also, compared to the non-welded base material, there is a substantial loss in mechanical properties. These factors cause the refusal of joining of these high strength alloys by conventional fusion welding methods. Therefore riveting has been widely used in aerospace structural constructions. This means production problems, increased weight, higher costs, and corrosion and stress concentrations around rivet holes. Friction Stir Welding (FSW) as a solid-state welding method is successfully addressing these issues.